An examination of personality in occupational outcomes: antagonistic managers, careless workers and extraverted salespeople. Issue 7 (7th February 2016) - Wells, Robert; Ham, Roger; Junankar, P. N. (Raja)
Abstract: This article investigates the role of personality in the sorting of individuals between a number of occupations, allowing for an extensive array of conditioning variables. The focus is an examination of the relationship between occupational outcomes and personality using the 'five-factor model'. We estimate a multinomial logit model using a panel data set from the Household Income and Labour Dynamics in Australia (HILDA) survey. Human capital variables are found to exhibit strong credentialism effects and there is evidence for some small dynasty hysteresis. Personality effects are found to be significant, relatively large and persistent across all occupations. The personality effects are strong enough to rival that of various education credentials. These personality effects include but are not limited to managers being less agreeable and more antagonistic; labourers being less conscientiousness; and salespeople being more extraverted.